2021
DOI: 10.3390/ani11051357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Activated Charcoal on Growth, Immunity, Oxidative Stress Markers, and Physiological Responses of Nile Tilapia Exposed to Sub-Lethal Imidacloprid Toxicity

Abstract: The existing study was designed to assess the influences of dietary activated charcoal (AC) on the growth performance, immune responses, antioxidative status, and its mitigating roles against the physiological responses of Nile tilapia exposed a sub-lethal dose of a neonicotinoid agriculture pesticide, namely, as imidacloprid (IMID). Nile tilapia juveniles were fed on diets supplemented with graded AC levels as 0 (control), 5, 10, 15, and 20 g/kg diet for eight weeks. Growth, hemato-biochemical indices, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The results showed high MDA levels in birds exposed to imidacloprid, while selenium nano form reduced the MDA level. Concisely, Emam et al [ 3 ] and Abd El-hameed et al [ 52 ] reported high MDA levels in birds exposed to imidacloprid. On the other hand, supplementation of selenium nano form reduced the MDA level in birds, as stated by Ibrahim et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed high MDA levels in birds exposed to imidacloprid, while selenium nano form reduced the MDA level. Concisely, Emam et al [ 3 ] and Abd El-hameed et al [ 52 ] reported high MDA levels in birds exposed to imidacloprid. On the other hand, supplementation of selenium nano form reduced the MDA level in birds, as stated by Ibrahim et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of oxidative stress, lipid peroxidation causes oxidative damage to cellular membranes, lipoproteins and other molecules containing lipids (Abd El-hameed et al, 2021). Lipids found in the cellular membrane are often targets of oxidative damage (Comporti, 1993).…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…For farmers, pests include mites and insects that feed on crops and aquatic plants, and cause animal and plant diseases, such as fungi, viruses, bacteria, snails, nematodes, and rodents [8]. On the other hand, pesticides are referred to as many chemical compounds that possess various biological activities and chemical natures, which are clustered together to increase their capability to eradicate pests [9][10][11][12][13]. Thus, as a broad definition, pesticides are all those substances or their mixture used for prevention, destruction, repelling, deterring, resisting, or controlling pests [8,9].…”
Section: Introductionmentioning
confidence: 99%